Willingness to pay for the vaccine in the Covid-19 pandemic: a lesson learned for future pandemic vaccine - Thang, Tran Binh; Hoang Lan Nguyen, Thi Anh Thu Dang, Nu Hong Duc Vo, Cao Khoa Dang, Thanh Gia Nguyen, Dinh Duong Le, Minh Tu Nguyen, Vu Van Ban Le, Duc Dan Nguyen, Huynh Thi Tuong Vy Le, Thi Hong Nhung Nguyen, Thi My Le Truong, Anh Thy Nguyen, Thi Thuy Trang (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
Our study aims to estimate the value of willingness-to-pay (WTP) for the COVID-19 vaccine and relevant factors in the central region of Vietnam. We conducted a cross-sectional survey among 367 people in Hue. To survey WTP, we used a contingent valuation method in a double-bounded dichotomous choice format. Multivariate median regression was applied to determine the predictors of WTP. The study involved 367 respondents with an age range of 18 - 74 years. Of these respondents, WTP for the COVID-19 vaccine was observed in 71.9% of participants, with a mean and median WTP amount of US38.20 and 28.87 for two doses. Age, knowledge of COVID-19, health insurance participation, belief in the effectiveness of the vaccine, and support from family/friends were found to be related to WTP. A high proportion of WTP was found, but the amount was low. Knowledge and beliefs related to vaccines were found to have an impact on the WTP amount. These findings can provide evidence for future consideration regarding vaccination campaigns and may contribute to tackling the barriers that block adequate vaccine coverage in the central region of Vietnam.